Social isolation among ageing population in Malaysia - Abdul Baqi, Norshafiqah Baljin; Abd Latif, Nurshafiqah; Mohd Saleh, Nurayuni Hanis; Md Yunus, Nurul Ain Shafika; Mohd Azlin, Nurin Aina Fatin Haziqah; Kunasekaran, Puvaneswaran; Rosnon, Mohd Roslan; Abdul Razak, Muhammad Afiq; Ibrahim, Rahimah (Human Resources Management Academic Research Society (HRMARS), 2024)
Social isolation is an increasingly significant issue within the social sciences and healthcare, particularly concerning aging populations. Defined by a deficiency in social interactions and meaningful relationships, social isolation has profound effects on the well-being of older adults. In Malaysia, the demographic shift towards an aging population, fueled by rising life expectancy and declining fertility rates, exacerbates the risk of social isolation. Contributory factors include deteriorating health, unemployment, and evolving family structures. This study explores issues related to social isolation among the elderly in Malaysia, including its contributing factors, impacts, and potential solutions for addressing these challenges. The findings underscore the urgent need for comprehensive interventions, such as policy reforms, community-based initiatives, and spiritual support programs, to improve the quality of life and foster social connectedness among older adults. The outcome also suggests that the main stakeholders especially government agencies, society members and the older adults must work together towards understanding and supporting the existing policies.